PEMANFAATAN BONEKA WAYANG DALAM PEMBELAJARAN BIPA LEVEL 6 GUNA MEMPERKENALKAN TOKOH INDONESIA - Nurul Hidayah; Khaerunnisa (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
One of the efforts made to introduce the charm, uniqueness and diversity of the Indonesian nation to audiences from various parts of the world is through BIPA teaching by utilizing the use of puppet media, the puppet media itself is used with the main objective of introducing great figures from Indonesia. Indonesian nation. Descriptive qualitative method is the method used by the author in this study. The material provided in the lesson has certainly been adapted to the standard of advanced level learners with BIPA Level VI teaching with the topic of discussion material